2016
DOI: 10.1371/journal.pone.0165267
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolites Predict Severity of Depression and Suicidal Ideation in Psychiatric Patients-A Multicenter Pilot Analysis

Abstract: Evaluating the severity of depression (SOD), especially suicidal ideation (SI), is crucial in the treatment of not only patients with mood disorders but also psychiatric patients in general. SOD has been assessed on interviews such as the Hamilton Rating Scale for Depression (HAMD)-17, and/or self-administered questionnaires such as the Patient Health Questionnaire (PHQ)-9. However, these evaluation systems have relied on a person’s subjective information, which sometimes lead to difficulties in clinical setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 62 publications
7
83
2
Order By: Relevance
“…glutamate and glycine) or as precursors of important neurotransmitters, such as catecholamines (from phenylalanine), histamine (from histidine), serotonin (from tryptophan) and γ-aminobutyric acid (from glutamate). Consistent with this, several studies have revealed associations between plasma amino acid patterns and depressive symptoms [5][6][7][8][9] however, the available evidence for older adults is less than that for younger populations. Because depressive symptoms in older adults differ from those of younger adults, the identification of the plasma amino acid signature of depressive symptoms in older adults is important not only for the development of a biomarker of geriatric depression, but also for understanding its pathophysiology.…”
Section: Introductionmentioning
confidence: 82%
“…glutamate and glycine) or as precursors of important neurotransmitters, such as catecholamines (from phenylalanine), histamine (from histidine), serotonin (from tryptophan) and γ-aminobutyric acid (from glutamate). Consistent with this, several studies have revealed associations between plasma amino acid patterns and depressive symptoms [5][6][7][8][9] however, the available evidence for older adults is less than that for younger populations. Because depressive symptoms in older adults differ from those of younger adults, the identification of the plasma amino acid signature of depressive symptoms in older adults is important not only for the development of a biomarker of geriatric depression, but also for understanding its pathophysiology.…”
Section: Introductionmentioning
confidence: 82%
“…Microglia play crucial roles in brain inflammation via releasing free radicals and inflammatory cytokines, such as interleukin‐6 and tumor necrosis factor‐α, and activation of microglia has recently been proposed to exist in various psychiatric disorders, including schizophrenia, depression, bipolar disorder, and autism . In addition, microglial overactivation is proposed to exist in the brains of suicide victims and suicidal individuals, especially via the tryptophan–kynurenine pathway . As noted above, a recent epidemiological data analysis showed that hikikomori sufferers are more likely to have suicide risk, thus similar biological mechanisms via microglial activation may exist in hikikomori …”
Section: Multidimensional Understandings Of Hikikomorimentioning
confidence: 93%
“…Tryptophan metabolites, especially serotonin, have gathered greater attention in the endeavor to understand the pathophysiology of depression . In addition, metabolites of the tryptophan–kynurenine pathway are increasingly attracting interest . Just recently, we reported that plasma tryptophan is a possible diagnostic biomarker of MDD and that some of the tryptophan–kynurenine metabolites in plasma are related to severity of some depressive symptoms .…”
Section: Methodsmentioning
confidence: 99%